PENGARUH OTONOMI PEREMPUAN TERHADAP PEMANFAATAN FASILITAS KESEHATAN SEBAGAI TEMPAT PERSALINAN DI KABUPATEN ENDE PROVINSI NUSA TENGGARA TIMUR - , Fransisca Nusamba Ero; , dr. Siswanto Agus Wilopo, S.U., M.Sc., Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: The use of health facility as a place of birth is an important issue to reduce maternal mortality. Womenâs autonomy is estimated to be influential to the use of health facility as a place of birth. Objective: To find out the effect of womenâs autonomy on the use of health facility as a place of birth and to find out the factors affecting womenâs autonomy on the use of health facility as a place of birth. Method: This was an analytical-observational study using a cohort prospective design and a quantitative approach. The subjects were pregnant women having examined their pregnancy to health facility in Ende District. The sample was taken with proportional random sampling as many as 242 women. The independent variable was womenâs autonomy and the independent variable was the use of health facility as a place of birth. Data analysis comprised univariable analysis using frequency and percentage distribution, bivariable analysis using chisquare test and multivariable analysis using simple logistic regression with Stata Program Version 11.0. Result: The bivariable analysis showed that there was no significant correlation between womenâs autonomy and the use of health facility as a place of birth with RR 1,0 (95%CI 0.93-1.14) and p-value >0.05 (0.5). The extraneous variable having a significant correlation with the use of health facility as a place of birth was womenâs occupation shown with RR 1.1 and p-value <0.05 (0.03). External variables associated with maternal age of women's autonomy is indicated with RR 2.2 (95% CI 1.22-3.96) and pvalues <0.05 (0.001), higher maternal education indicated with RR 1, 8 (95% CI 1.30-2.53) and p-values <0.05 (0.002)